In situ photochemical formation of defect-related fluorescent ZrO2 nanoparticles in solution and within UV-cured EA/TPGDA coatings - Akman, Onur; Ozcelik Kazancioglu, Elif; Arsu, Nergis (TAYLOR & FRANCIS INC, 2025)
In this study, in situ photochemical synthesis of tetragonal-ZrO2 nanoparticles (t-ZrO2 NPs) was performed both in N,N-dimethyl formamide/water solution and within an epoxy diacrylate/tripropylene glycol diacrylate polymer matrix. The photoreduction of ZrCl4 to t-ZrO2 NPs was conducted, and upon UV irradiation, ZrCl4 undergoes photochemical decomposition facilitated by radicals generated from Irgacure 2959. These radicals promote Zr-Cl bond cleavage followed by hydrolysis and oxidation, leading to the formation of Zr-O-Zr linkages and, ultimately, ZrO2 NPs. The formation of ZrO2 NPs was confirmed by the appearance of a defect-related absorption band in the UV-Vis spectrum, accompanied by enhanced fluorescence emission arising from oxygen vacancies and Zr-3+ centers. Thermogravimetric analysis was used to determine the thermal properties, and photopolymerization kinetics were studied using photo-differential scanning calorimetry, and the rate of polymerization and double bond conversions (DBC%) were calculated. Among all samples, the formulation containing 4 wt% ZrCl4 (A4) showed the highest polymerization efficiency, with a DBC of 81%. Crystallographic properties and surface morphology were evaluated by X-ray diffraction and FE-SEM analysis, respectively. Formulation A2 resulted in the most hydrophilic surface. Efficient photocatalytic degradation of methylene blue dye was achieved with 98% degradation in a solution containing t-ZrO2 NPs.
Keywords: In situ photochemical synthesis; fluorescence emission; fluorescent t-ZrO2 nanoparticles; epoxy acrylate/TPGDA; PHOTOPOLYMERIZATION; CORROSION; ZIRCONIA; PHOTOINITIATOR; LUMINESCENCE; CERAMICS; ACID; Polymer Science